Dynamic linkage between Macroeconomic Activities and Stock Prices in Fiji - Puah, Chin-Hong; Jayaraman, T.K (Universiti Malaysia Sarawak, (UNIMAS), 2007)
This paper seeks to investigate whether there is any causal relationship between capital stock prices and macroeconomic activities in Fiji. Empirical results show that all the time series data are nonstationary and cointegrated with a single vector. All the explanatory variables have been found to contribute to the long-run equilibrium relationship. The estimation of error-correction model further confirms that stock price index is cointegrated with real economic activities in the long run, and it adjusts rather fast from short-run deviations towards the long-run equilibrium level. Except for interest rate, real output, M2 and exchange rate do Granger cause stock prices in the short-run.